Surgical disorders of the peripheral nerves - Birch, Rolfe (Springer, 2011)
Since the highly praised first edition of Surgical Disorders of the Peripheral Nerves was published in 1998, greater understanding of the molecular and cellular events which underlie the response of nerves to injury, regeneration and neuropathic pain has been achieved. This second edition has been fully updated in line with new clinical knowledge, and also incorporates the extensive study of thousands of surgical case studies spanning repairs of the supraclavicular plexus in the adult, the birth lesion of the brachial plexus, compound nerve injury and iatrogenous injury. Beginning with the fundamentals of the anatomy and function of the peripheral nervous system, and working its way through various types of injury, operative methods, the regeneration and recovery of nerves, surgical reconstruction, pain, and rehabilitation, this eloquently written work provides the reader with the solid understanding required to successfully perform surgery on the peripheral nervous system. Dr Shelagh Smith, joined by Dr Ravi Knight, has rewritten the chapter Electrodiagnosis.  Professor Tara Renton has written a new chapter on injuries to the trigeminal nerve in maxilla-facial and dental work.  The drawings, by Mr Philip Wilson, are new.  Most of the 700 illustrations are also new. This thorough and authoritative look at the surgical treatment of the peripheral nerves is fully illustrated throughout with exquisite line diagrams and clear, instructive photographs.